How Baguazhang Incorporates Theory from the Book of Changes - Joern, Travis (Revista de Artes Marciales Asiáticas, 2012)
In this article, the author examines how a martial artist can apply the theoretical aspects of the Yijing to his or her training, and tries to determine why baguazhang practitioners chose this particular text as the core of their system. Through this, we can study some of the ways that baguazhang was linked to the culture in which it was developed.